Social Values in the Poem Tak Harus Sedarah Menjadi Saudara by Eko Saputra Poceratu (A Sociological Study of Literature) - Seknun, Ermyanti; Ratumalessy, Merlyn (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study seeks to discover and elucidate the social values embedded in the poem Tak Harus Sedarah Untuk Menjadi Saudara by Eko Saputra Poceratu. This research employs a literary sociology approach through qualitative methodology. The data analysis method employs descriptive techniques to elucidate the social values embedded in the poem Tak Harus Sedarah Untuk Menjadi Saudara by Eko Saputra Poceratu. The research indicates that there are five data points in the poem Tak Harus Sedarah Untuk Menjadi Saudara by Eko Saputra Poceratu, which were assessed through a sociological literary approach. The data is categorized into three types of moral values, one type of religious value, and one type of prevailing value. The predominant social value data in the poem Tak Harus Sedarah Untuk Menjadi Saudara by Eko Saputra Poceratu pertains to moral ideals.